PENGARUH IKLIM ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING - Iffah Nurtaria Rohmah; Uju Suji’ah (Bajang Institute, 2024)
This research aims to determine the influence of organizational climate and job satisfaction on employee performance through work discipline as an intervening variable. The sampling technique used a saturated sampling technique with a total of 45 respondents who were employees at the Personnel, Education and Training Agency (BKPP), Sleman. The analysis test tool uses Smart PLS V.4 with the SEM (Structural Equation Modeling) analysis method. The research results show that 1). Organizational climate does not have a significant influence on work discipline; 2). Job satisfaction has a significant influence on work discipline; 3). Organizational climate has a significant influence on employee performance; 4). Job satisfaction does not have a significant influence on employee performance; 5). Work discipline has a significant influence on employee performance; 6). Indirectly, organizational climate has no influence on employee performance through work discipline; 7). Indirectly, job satisfaction has no influence on employee performance through work discipline